Animal production and rainfed agriculture in Asia: Potential opportunities for productivity enhancement - Devendra, C. (SAGE Publications, 2000)
Asia is a region of dynamic economic changes, fuelled by rapid population growth, urbanization, increased incomes, demand-led processes and changing consumer preferences for foods of animal origin. The projected total meat and milk consumption levels for 2020 are far in excess of anticipated supplies, and place unprecedented pressure on the management of natural resources (crops, animals, land and water). Increased productivity in the future will need to come from improved per animal performance, appropriate animal production systems, and higher efficiency in the use of feed resources. Unlike the demand-driven, intensive and private-sector-led non-ruminant sector, ruminant production systems have lagged behind in productivity because they are largely in the hands of resource-poor small farmers. Since existing irrigated lands are overused, the potentially important rainfed lands will become increasingly important in the future for productivity enhancement, justifying increased resource use. A strong systems research approach to rainfed agriculture, together with interdisciplinarity, a holistic focus and community-based participation, is necessary. This effort needs to be supported by increased research investment and a policy environment that can provide for major socioeconomic benefits, improved livelihoods of the poorest of the poor, agricultural growth, and environmental sustainability. Topics of discussion include animal production trends, animal production in rainfed mixed farming systems; rainfed environments; feed resources and nutrition; strategy for feed resource use; challenges for research and development; and research investments.